PRAWN FISHERY BY TRAWL OFF CANNANORE DURING 1965-1968 - Kuthalingam, M D K (Indian Journal of Fisheries, 2011)
The prawn catches by trawl off Cannanore have been assessed from the landingdata of the shrimp trawlat depths 15-26 m during January 1965 to June 1968. Annuallyan average catch of 624 tonnes of prawns was landed by the mechanised boats at Cannanore.The catch rates and the dominant size ranges and the depth-wise distribution of the differentspecies of prawn which formed the bulk of the fishery during different months arealso given.